(untitled) (Damascus University Journal for the economic and Political sciences, 2025)
The research aimed to test the impact of the stages of the companies’ life cycle. By practicing on the accounting conservatism policy in the financial reports of companies. Listed on the Damascus Stock Exchange by testing the effect of each stage of the life cycle of the companies in the research sample. Since their listing in 2006 until 2022, where not all companies had included their reports for the year 2023 at the date of preparing the research. The Dickenson (2011) model was to distinguish the stages of the companies’ life cycle and the market value to book value model to test the (unconditional) accounting conservatism policy. Some of the following results: Most of the companies in the research sample practiced (unconditional) accounting conservatism. In addition, most of the companies in the research sample were in the mature stage. In addition, the effect of the presentation stage and the Growth stage on the practice of accounting conservatism was weak and inverse, while in the mature stage and the Growth stage Decline was positive and significant.